2000
DOI: 10.1590/s0074-02762000000600019
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study on the different staining methods and number of specimens for the detection of acid fast bacilli

Abstract: The presence of acid fast bacilli in multiple specimens was investigated comparatively with ZiehlNeelsen (ZN)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
31
0
4

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 6 publications
7
31
0
4
Order By: Relevance
“…Our results were similar with. Prasanti K, 9 Cheng AG, 10 Sethi S, 11 Singh NP, 12 Ulukanligil M, 13 and Jain A 14 in their studies which also found AR stain was more sensitive in comparison with ZN stain for the diagnosis of tubercular bacilli. Thus it is concluded that, for detection of AFB in paucibacillary specimen, AR is much more sensitive than ZN staining technique.…”
Section: Discussionmentioning
confidence: 90%
“…Our results were similar with. Prasanti K, 9 Cheng AG, 10 Sethi S, 11 Singh NP, 12 Ulukanligil M, 13 and Jain A 14 in their studies which also found AR stain was more sensitive in comparison with ZN stain for the diagnosis of tubercular bacilli. Thus it is concluded that, for detection of AFB in paucibacillary specimen, AR is much more sensitive than ZN staining technique.…”
Section: Discussionmentioning
confidence: 90%
“…A diagnose por meio do exame anátomo-patológico, coloração para bacilos álcool-ácido-resistentes (BAAR), métodos de imunohistoquímica, teste tuberculínico e cultura são exames importantes para o diagnóstico diferencial. Observa-se, freqüentemente, em formas paucibacilares da doença que a pesquisa de BAAR, a imunohistoquímica e as culturas são negativas (Hsu et al, 1981;Wiley et al, 1991;Taippeiner, Wolf, 1993;Kox, 1995;Kutzner et al, 1998;Bollela et al, 1999;Ulukanligil et al, 2000;Ferreira et al, 2002).…”
Section: Lista De Abreviaturasunclassified
“…Por outro lado, o exame histológico de lesões fixadas em formol e emblocadas em parafina freqüentemente não detecta a presença de bacilos ou estes são encontrados em pouca quantidade, o que determinou numerosas modificações da técnica clássica de Ziehl-Neelsen (Ulukanligil et al, 2000).…”
Section: Pesquisa De Baarunclassified
See 2 more Smart Citations